little people, big dreams : elton john - Vegara, Maria isabel sanchez (Spain Alba editorial, 2020)
This Little People, Big Dreams book tells the life story of Elton John, from his childhood playing the piano in London to his rise as a musical superstar. It highlights his partnership with Bernie Taupin, his unique style, and his journey toward finding personal happiness and supporting LGBTQ rights.